TIPE DAN METODE PENGAMBILAN KEPUTUSAN ANGGARAN PENDIDIKAN - Trisharsiwi Trisharsiwi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Â Abstract:This study aims to describe the characteristics of the type and method of decision makingin the education budgetTaman Muda Ibu Pawiyatan Tamansiswa Yogyakarta. Researchc arried out for six months with research subjects Ibu Pawiyatan chief, Chairman of the Taman Muda Ibu Pawiyatan, teachers at Taman Muda Ibu Pawiyatan, treasurer, some of the staff involved in the preparation of the budget, the parents of students involved in the sourcing offunds, and people who are always critical in every decision making and budgeting, both at the level ofthe Assembly Ibu Pawiyatan or in part Taman Muda Ibu Pawiyatan. Data were collected by in depth interviews, observation, and documentation. Data were analyzed with data analysis techniques Hubermanand Milesversion consisting of data reduction, data presentation, and conclusion.The results showed that the characteristics of the type of education budget decision making principals is situational, sometimes using his authority, but incertain situations involving subordinates democratically. The results also showthat the characteristics of the education budget decision making method is selective minority principals, seniority, and scientific authoritarian.Â